(untitled) (Research, Society and Development, 2021)
The inflammatory process is a response of the immune system to some harmful stimulus that can be transmitted by physical, chemical, microbiological trauma or even complete the for, that is, it can be generated by bacteria, viruses, fungi and by some external factors such as heat or physical trauma. NSAIDs are non-steroidal anti-inflammatory drugs that have three functions: Anti-inflammatory, analgesic and anti-thermal, the mechanism of action of this class consists of inhibiting the arachidonic acid cascade, a two-way substrate: the Lipoxygenase (LOX) pathway and the life of Cyclooxygenase (COX). When arachidonic acid is converted by COX, it produces as prostaglandins and thromboxane, inhibiting as cyclooxygenases I and II and thus initiating the recurrent symptoms of inflammation. Cycoxygenase I has a constitutive function and is present in the gastric and renal mucosa, in the kidneys, it contributes to physiological functions, with a vasodilator effect, acts on the nervous system and on the renin-angiotensin-aldosterone system, regulating the blood flow in the blood flow. NSAIDs inhibit the COX enzyme, which can result in several acute or chronic kidney damage, in chronic use the risk increases in several nephrotoxicities.